Pengaruh DER, ROA dan NPM Terhadap Return Saham Perusahaan Properti Terdaftar Di BEI Periode 2017-2020 - Sari, Dian Indah; Maryoso, Slamet (PROFITABILITAS, 2022)
Abstract - This study aims to determine the effect of DER, ROA and NPM on stock returns of property companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This type of research is descriptive quantitative. Literature study was used as a data collection method, namely the data in this study were obtained from journals, literature studies and books related to the research topic. Classical Assumption Test is a data analysis technique used in this study using the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, T Test and Coefficient of Determination Test. Based on the results of the discussion above, the following conclusions are obtained: First, the DER variable has a positive and significant influence on stock returns of property companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Second, the ROA variable has a positive and significant effect on stock returns of Property companies listed on the IDX for the 2017-2020 period. Third, the NPM variable has a positive and significant effect on stock returns in Property companies listed on the IDX for the 2017-2020 period. Fourth, the variables DER, ROA and NPM simultaneously have a significant and positive effect on stock returns of property companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Keywords: DER, ROA, NPM